Investigate the therapeutic effect of autologous adipose-derived stem cells (ADSCs) on ischemic renal failure in dogs. - Bassim K .Khashjoori1 , M. S. Ghaji1 , Omar Tariq Hammoodi2 , Majid A. Alkhilani2 , Ali. A. Ajeel 3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background/ aim: The kidney excretes waste materials and regulates important metabolic functions, andrenal disorders constitute a significant medical problem and can result in fatalities. In the present study,mesenchymal stem cells derived from canine adipose tissue were isolated and evaluated for their ability toimprove renal function in a canine model of ischemic renal failure. Materials and Methods: The canineischemic renal failure model was developed by a traumatic occlusion of the renal artery in 10 dogs. ASCswere administered directly into the renal artery following ischemic renal failure induction. Blood analysisand histological parameters were analyzed. Results: The group treated with ASCs had decreased blood ureanitrogen and creatinine levels, and showed an improving histological manifestation. ASCs were detectedaround the tubules of these kidneys at the histological level. Conclusion: our findings suggest that ASCscould be an alternative therapeutic agent for canine ischemic renal failure.